Mathematical connection skills of junior high school students in solving system of linear equations in two variables problems - Luluk Sulistiyowati; Indah Wahyuni (Universitas Muhammadiyah Malang, 2024)
Students mathematical connection skills are valuable dimension that teachers must put into consideration so that students can develop and link their mathematical skills with knowledge beyond Mathematics. This research aimed to analyze the mathematical connection skills of Junior High School students when solving the System of Linear Equations in Two Variables (Sistem Persamaan Linear Dua Variabel/SPLDV) problem. Students mathematical connection skills are valuable dimension that teachers must put into consideration so that students can develop and link their mathematical skills with knowledge beyond Mathematics. This research aims to analyze the mathematical connection skills of Junior High School students when solving the SPLDV problem. This research made use of Qualitative approach by which 18 students of grade VIII from SMP Argopuro 1 Panti Jember, East Java, participated. Mathematical connection skill test and interview guideline were conducted for this research. Data triangulation technique was used to process and compile data for the research report. The findings of the research discovered that students with high level of mathematical connection skills were able to relate and implement their knowledge to different kinds of situations, and students with medium level of mathematical connection skills were only able to apply their knowledge to simple situations, meanwhile students with low level of mathematical connection skills were unable to relate and implement their knowledge to a variety of situations.